ERRORS OF STUDENTS LEARNING WITH REACT STRATEGY IN SOLVING THE PROBLEMS OF MATHEMATICAL REPRESENTATION ABILITY - Sari, Delsika Pramata; Darhim, Darhim; Rosjanuardi, Rizky (Journal on Mathematics Education, 2018)
The purpose of this study was to investigate the errors experienced by students learning with REACT strategy and traditional learning in solving problems of mathematical representation ability. This study used quasi experimental pattern with static-group comparison design. The subjects of this study were 47 eighth grade students of junior high school in Bandung consisting of two samples. The instrument used was a test to measure students' mathematical representation ability. The reliability coefficient about the mathematical representation ability was 0.56. The most prominent errors of mathematical representation ability of students learning with REACT strategy and traditional learning, was on indicator that solving problem involving arithmetic symbols (symbolic representation). In addition, errors were also experienced by many students with traditional learning on the indicator of making the image of a real world situation to clarify the problem and facilitate its completion (visual representation).DOI: http://dx.doi.org/10.22342/jme.9.1.4301.121-128